Crucius’s Conception of Historicity as a Process of Self-Cultivation in the Context of German Enlightenment - Bojda, Martin (Dějiny – teorie – kritika, 2016)
Marking a double anniversary of the German Enlightenment philosopher and theologian Christian August Crucius, this study aims at presenting his contribution to a modern understanding on historicity and culture. The author explains Crucius’s opposition to the direction of German Enlightenment represented by Leibniz and Wolff, and emphasises the originality of Crucius’s concept, which takes as its starting point the organicism of metaphysics based on Christian foundations, while rejecting many influential logical methods. The exposition focuses on deducing historicity from reflexivity that transcends organicity in the sense of mere reproduction and integrates its creative potential by cultivating the understanding of derivativeness and contextuality of its own development. In bringing together the principle of historicity with ethics, Crusius’s project can be compared to Schleiermacher’s later undertaking, while its basic focus on cultural and social immanence is shared with the work of Herder and other German authors of the second half of the 18th century.